The Corelation between the Duration of Using Waterproof Foundation and the Incidence of Acne Vulgaris in Female University Students - Silvi Fitriyanti; Masfiyah Masfiyah; Yuzza Alfara; Hesti Wahyuningsih Karyadini (Journal of Advanced Multidisciplinary Research, 2022)
Acne vulgaris (AV) is a chronic inflammatory disease of the polysebaceous follicles of the skin. Lesions that can be caused by AV can be in the form of papules, pustules, modules, or comedones. Based on a preliminary study, many UNISSULA Medical Faculty students have AV and many use foundation. The purpose of this study was to determine the relationship between the duration of using foundation and the incidence of AV in Unissula Medical Faculty students. This research is an observational study with a cross sectional design. The sample is a student of FK UNISSULA Class of 2019 and 2020 who uses a waterproof foundation. The exclusion criteria for the sample were students who had not passed the module, had many activities so that they slept < 6 hours, one week before the exam, one week before and during menstruation. There were 47 respondents of UNISSUA FK female students, 17 (36.2%) female students suffered from AV and 30 (63.8%) female students did not suffer from AV. The average duration of using waterproof foundation is 4.5 hours. The results of the analysis of the relationship between the duration of using the foundation and the incidence of AV using the Spearman test obtained p 0.001, with r -0.482. The conclusion in this study was that there was a relationship between the duration of using the foundation and the incidence of AV with a moderate correlation.